Conjunto mixto, Bielefeld [Alemania] - Kresing, Raines M. (2000)
Transformación de una fábrica en la manzana de viviendas
Keywords: ALEMANIA; BIELEFELD; CONJUNTOS HABITACIONALES; REFUNCIONALIZACION ARQUITECTONICA